2014
DOI: 10.1007/s10823-014-9234-9
|View full text |Cite
|
Sign up to set email alerts
|

Nativity Status and Sources of Care Assistance Among Elderly Mexican-Origin Adults

Abstract: Much like other racial/ethnic groups, Latinos are facing challenges to provide needed care to aging adults. Older Latinos underutilize nursing homes and home health care services and primarily rely on their families for assistance. While this general trend has been established, little attention has been paid to nativity differentials in patterns of caregiving for this segment of the aging population. The analyses are based on the latest wave (Wave 7) of the Hispanic Established Population for Epidemiologic Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 42 publications
0
27
0
1
Order By: Relevance
“…We found that caregivers of foreign-born older adults report more care burden than caregivers of U.S.-born older adults. Previous studies on caregiving in immigrant families show that foreign-born care recipients tend to be more dependent on one focal child for help and less likely to rely on other relatives for late-life health support ( Angel et al, 2014 ; Rote & Moon, 2018 ). Our results supported these findings in that caregivers of foreign-born older adults provided more help with ADLs and IADLs, medical care and medical insurance, and appointments than care recipients of U.S.-born older adults.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that caregivers of foreign-born older adults report more care burden than caregivers of U.S.-born older adults. Previous studies on caregiving in immigrant families show that foreign-born care recipients tend to be more dependent on one focal child for help and less likely to rely on other relatives for late-life health support ( Angel et al, 2014 ; Rote & Moon, 2018 ). Our results supported these findings in that caregivers of foreign-born older adults provided more help with ADLs and IADLs, medical care and medical insurance, and appointments than care recipients of U.S.-born older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The current study only included the primary caregivers (who spent more time than other available caregivers) from the data and a large portion of care recipients are dependent on a daughter or son who may face multiple social roles (e.g., employment and child/other family care). Possibly, caregivers may experience or perceive more demands from their foreign-born care recipients compared to caregivers of U.S.-born older adults ( Angel et al, 2014 ; Rote & Moon, 2018 ). However, when the interactions between care recipient nativity status and caregiver’s race/ethnicity and all covariates were considered, care recipient nativity status was no longer significant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations